2019
DOI: 10.1002/mcf2.10071
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Growth and Reproductive Dynamics of Red Drum in the Northern Gulf of Mexico

Abstract: The Red Drum Sciaenops ocellatus stock is heavily targeted in the Gulf of Mexico (GOM) by recreational fishers and supports a small commercial fishery in Mississippi. Despite their popularity, little recent work has been done to describe their life history. In this work, we describe sex‐specific growth and reproductive dynamics of Red Drum collected from the northern GOM from September 2016 through October 2017. We evaluated seven candidate growth models and found that the three‐parameter von Bertalanffy growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(97 reference statements)
1
4
0
Order By: Relevance
“…The GLM comparing TL to age, sex, and season suggested that age and season were explanatory, whereas sex and the age × sex interaction were not (Table 1). These results were consistent with previous studies suggesting that growth trajectories change significantly after age 4 (Ross et al 1995), thus hindering mathematical modeling of growth in Red Drum across a broader range of ages with a simple single‐stage growth function (Ross et al 1995; Porch et al 2001; Bennetts et al 2019). For this reason, we used only age‐4 and younger individuals for subsequent analyses, which nevertheless constituted the bulk of the observed estuarine population.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The GLM comparing TL to age, sex, and season suggested that age and season were explanatory, whereas sex and the age × sex interaction were not (Table 1). These results were consistent with previous studies suggesting that growth trajectories change significantly after age 4 (Ross et al 1995), thus hindering mathematical modeling of growth in Red Drum across a broader range of ages with a simple single‐stage growth function (Ross et al 1995; Porch et al 2001; Bennetts et al 2019). For this reason, we used only age‐4 and younger individuals for subsequent analyses, which nevertheless constituted the bulk of the observed estuarine population.…”
Section: Resultssupporting
confidence: 90%
“…A singular sex‐aggregated growth trajectory was assumed if the likelihood ratio for inclusion of the age × sex term did not significantly improve the model. Although sex‐based differences in growth have been observed in Red Drum, these differences typically manifest after sexual maturity, and aggregated growth functions perform reasonably well in age‐classes younger than 5 (Bennetts et al 2019; Hightower et al 2022). Upon observation of no growth differences between sexes for ages 0–4 (see Results), sex‐aggregated point estimates of mean length at age were obtained from otolith‐aged individuals that were collected in each season (i.e., seasonal mean length at age).…”
Section: Methodsmentioning
confidence: 99%
“…There are a few examples of sciaenids where males and females mature at similar sizes (e.g. S. ocellatus , Bennetts et al., 2019) and further research into exploring the possible mechanisms for these differing life history strategies is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…ocellatus, Bennetts et al, 2019) and further research into exploring the possible mechanisms for these differing life history strategies is warranted.…”
Section: Oocyte Development and Gonad Histologymentioning
confidence: 99%
“…Despite the presence of precocious cysts, the males sampled in this study were considered functionally immature (prepubertal) as they did not have enough spermatozoa in the testes to successfully fertilize eggs. However, they would be considered physiologically mature (post-pubertal) based on the literature (see Bennetts et al, 2019;Lowerre-Barbiere et al, 2016). To our knowledge, precocious cysts within the gonad in a highly advanced stage of gonadal development have not been described in the literature for any sturgeon or teleost species.…”
Section: Discussionmentioning
confidence: 99%